Proteoglycan forms of the lymphocyte homing receptor CD44 are alternatively spliced variants containing the v3 exon. - Jackson, D; Bell, J; Dickinson, R; Timans, J; Shields, J; Whittle, N (1995)
The CD44 cell surface glycoprotein is expressed on a broad range of different tissues as multiple isoforms containing from one to ten alternatively spliced exons v1-v10 inserted within the extracellular domain. Differential glycosylation generates still further variability, yielding both N- and O-glycan-modified forms of CD44 in addition to proteoglycan-like variants containing chondroitin sulphate and heparan sulphate. These high molecular mass proteoglycan-like variants, previously identified in lymphocytes, melanomas, and keratinocytes have been implicated in cell-matrix adhesion, cell motility, and invasiveness. More recently, monocyte CD44 molecules presumed to carry glycosaminoglycan chains were shown to bind the chemokine MIP-1 beta (Tanaka, Y.,D. H. Adams, S. Hubscher, H. Hirano, U. Siebenlist, and S. Shaw. 1993. Nature (Lond). 361:79-82.) raising the intriguing possibility that proteoglycan-like CD44 variants might play a role in regulating inflammatory responses. Here we have investigated the molecular identity of these proteoglycan-like CD44 variants by generating a panel of recombinant CD44 isoforms using a novel cassette cloning strategy. We show that both chondroitin and heparan sulphate modifications are associated specifically with isoforms (CD44v3-10 and CD44v3,8-10) containing the v3 alternative exon which encodes a consensus motif SGXG for GAG addition. Other isoforms (CD44v10, CD44v8-10, CD44v7-10, and CD44v6-10) are shown to lack these GAG chains but to carry extensive O-glycan modifications, most likely within the mucin-like alternative exon inserts. We also demonstrate that the majority of endogenous GAG-modified CD44 isoforms present in epithelial cells constitute v3 isoforms thus establishing that in these cells the majority of proteoglycan-like CD44 variants are generated by alternative splicing. Finally we present evidence using transfected B lymphoma cells that the GAG-modified CD44 isoforms CD44v3-10 and CD44v3,8-10, unlike CD44H, bind only weakly to hyaluronan. Together with the demonstration in the accompanying paper (Bennett, K., D. G. Jackson, J.C. Simon, E. Tanczos, R. Peach, B. Modrell, I. Stamenkovic, G. Plowman, and A. Aruffo. 1995. J. Cell Biol. 128:687-698.), that CD44 molecules containing the v3 exon bind growth factors, these results highlight a new and potentially important role for CD44 alternative splicing in the control of cell-surface proteoglycan expression.